The grand energy transition : the rise of energy gases, sustainable life and growth, and the next great economic expansion - Hefner, Robert A., 1935- (Hoboken, N.J. : Wiley, 2009)
"A groundbreaking book on solving our growing energy problems. In this visionary book, leading energy industry executive Robert Hefner puts forth a convincing case about how the world can move beyond its current dependence on oil and toward a new era of clean, renewable energy. Written with the knowledge and authority of a major player in this industry, Hefner relates how misguided government policies and vested industry interests have contributed to our current energy problems and proposes a variety of measures that could encourage the use of natural gas, solar, wind, and hydrogen. Convincingly makes the case that natural gas is the essential bridge fuel to a new era of clean, renewable energy sources. Details how natural gas can help break our oil and coal dependency. Offers a sweeping, historic picture of the world energy situation. Presents a compelling and provocative case that natural gas is key to our short-term energy problems. A well-written and engaging book that mixes personal anecdotes and experiences with insightful analysis, The Grand Energy Transition is a powerful argument about how we can best solve our toughest energy problems"--Provided by publisher.
0
Includes bibliographical references and index.
Keywords: Renewable energy sources; Energy policy